2023
DOI: 10.1007/s40803-022-00188-4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Freedom as a Defensive Right

Abstract: Ensuring the proper implementation of academic freedom can be difficult both for policymakers and university authorities. Hence, great emphasis should be given to the defensive function of academic freedom. In this paper, we analyse the legal regulations and the jurisprudence of the constitutional courts of Germany, Hungary, Poland, Portugal, and Spain. We identify who is the holder of academic freedom, how the defensive function of academic freedom works and what academic activities are being protected. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…By examining the decisions of constitutional courts, we have shown that individuals may disagree with this cost so strongly that they seek the protection of their rights before the court. Our study confirms the findings of Stachowiak‐Kudła et al (2023) that the university's rights to institutional autonomy and academic freedom appear as major lines of legal argumentation. Of course, these findings presuppose a selection of countries that protect academic freedom and university autonomy on a constitutional level for our sample.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…By examining the decisions of constitutional courts, we have shown that individuals may disagree with this cost so strongly that they seek the protection of their rights before the court. Our study confirms the findings of Stachowiak‐Kudła et al (2023) that the university's rights to institutional autonomy and academic freedom appear as major lines of legal argumentation. Of course, these findings presuppose a selection of countries that protect academic freedom and university autonomy on a constitutional level for our sample.…”
Section: Discussionsupporting
confidence: 92%
“…The literature on the university's right to institutional autonomy and academic freedom states that because these rights are rarely defined in constitutions or legal documents, constitutional courts are often asked for an interpretation of these rights (Stachowiak‐Kudła et al, 2023). This demand for a proper interpretation in cases of university mergers becomes clear in our cases (see Appendix Table A2).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars attached to higher education systems in countries are considered as “democratic knowledge‐over‐force” who act against violence and undemocratic behaviors of powerholders. In case of undemocratic behaviors of powerholders, scholars are the prime activists who make general public aware of such incidences being the models and teachers of democratic values (Stachowiak‐Kudla et al., 2023).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Stachowiak‐Kudla et al. (2023) argue that higher education communities play an important role in developing the skills and knowledge of their people as teachers of democratic values. This role of enhancing awareness of democratic values is feasible only with a reasonable degree of academic freedom, and thus academic freedom is a pre‐requisite in promoting democracy in societies.…”
Section: Literature Survey and The Hypothesismentioning
confidence: 99%
“…Building on the rich literature on academic freedom that sprang up over the last few years (Karran & Mallinson, 2019;Kinzelbach et al, 2022;Ramanujam & Wijenayake, 2022;Stachowiak-Kudła, 2021;Stachowiak-Kudła et al, 2023), we theorize that academic freedom fosters greater degrees of democratic development.…”
Section: Academic Freedom and Higher Educationmentioning
confidence: 99%